CAUSES OF COMPLICATIONS OF THE LUNG ARTIFICIAL VENTILATION APPARATUS CHARACTIRISTICS - Yovkochev D. SH.; Krasninkova M. B.; Kenjayev L. T. (Scholars Digest Publishing, 2024)
The article is devoted to the peculiarities of the diagnosis of post-intubation complications, in particular, tracheal stenosis. The materials of treatment of 132 patients with neurosurgical and neurological profiles during prolonged intubation were studied. A retrospective analysis of 263 autopsies was carried out. Postmortem changes in tracheal tissue were noted in 4.5% of men and 0.7% of women. A prospective analysis revealed various postintubation complications in 69% of patients. Early complications prevailed (4-6 days) endobronchitis 2 and 3 art. in 13.6%, bedsores of the trachea and fibrin tracheitis in 7.6%, bedsores of the vocal cords in 3.8%, edema of the supravascular space in 3%. Late complications (more than 10 days) were represented by inflammatory stenosis in 9.8%, cicatricial stenosis in 6.8%, tracheoesophageal fistula in 1.5%. Expiratory stenosis (supra or infrastenotic malformation) occurred in 6.9% of patients. Postintubation complications are more common in men than in women; postmortem changes in the trachea are 15 times lower than the frequency of life-time diagnosed postintubation complications. There was no connection between purulent endobronchitis and the frequency of tracheal stenosis formation.
Keywords: prolonged tracheal intubation; complications; fibrotracheobronchoscopy stenosis.